Comprehensive analysis of cutaneous T‐cell lymphoma (CTCL) incidence and mortality in Canada reveals changing trends and geographic clustering for this malignancy. Issue 18 (10th May 2017) - Ghazawi, Feras M.; Netchiporouk, Elena; Rahme, Elham; Tsang, Matthew; Moreau, Linda; Glassman, Steven; Provost, Nathalie; Gilbert, Martin; Jean, Sara‐Elizabeth; Pehr, Kevin; Sasseville, Denis; Litvinov, Ivan V.
Abstract : BACKGROUND: Previous reports of geographic clustering of cutaneous T‐cell lymphoma (CTCL) in Texas, Pittsburgh, and Sweden as well as the occurrence of CTCL in married couples and family members raise a possibility of the existence of an external and potentially preventable trigger(s) for this rare skin cancer. METHODS: The authors studied CTCL incidence and mortality in Canada using 3 distinct population‐based cancer databases. Data on patients' sex, age at the time of diagnosis, subtype of CTCL malignancy, reporting province, city, and postal code were analyzed. CTCL cases were mapped across Canada using geographic information systems software. RESULTS: In total, 6685 patients with CTCL were identified in Canada during 1992 through 2010 (CTCL incidence rate, 11.32 cases per million individuals per year), of which 58% were males. The mean age at diagnosis was 59.4 ± 21.5 years. Geographic analysis of patients revealed increased CTCL incidence on the provincial and city levels in several eastern provinces and in Manitoba. An analysis according to postal codes (Forward Sortation Area [FSA]) identified select communities in which several high‐incidence FSAs were contiguous or adjacent. Several of these FSAs were located in industrial regions of Canadian cities. Conversely, 3 of 8 low‐incidence FSAs were clustered in Ottawa, Ontario, which has very little industrial presence. An analysis of CTCL mortality in Canada corroborated the current incidence findings. CONCLUSIONS: The current results provide a comprehensive analysis of CTCL burden in Canada and highlight several important areas of geographic case clustering. These findings argue that industrial exposures may play an important role in promoting CTCL pathogenesis. Cancer 2017;123:3550‐67. © 2017 American Cancer Society . Abstract : Cutaneous T‐cell lymphoma demonstrates nonrandom distribution with case clustering in industrial areas of Canada and spares cities with a low industrial presence. These findings argue for the existence of a potentially preventable external trigger for this rare skin cancer.